Al3+ ‐ Phenanthroline Xerogel for Dual Application: Catalyst for Knoevenagel Condensation and Fluorescent Chemosensor for Azo Dyes. Issue 12 (12th August 2016) - Rambabu, Darsi; Pooja,; Pradeep, Chullikkattil P.; Dhir, Abhimanew
Abstract: New Al 3+ metal co‐ordinated organic xerogel (namedAlPDAX ) based on 1, 10‐phenanthroline‐2, 9‐dicarboxylic acid is synthesized. Xerogel is characterized by TGA, FTIR, PXRD and SEM analysis. XerogelAlPDAX is evaluated for its catalytic activity in Knoevenagel condensation reaction. It shows a good catalytic activity and recyclability even after 5 cycles. Xerogel being fluorescent in nature is also utilized as template for recognition of industrially relevant azo dyes with help of fluorescence spectroscopy. It was observed that most of the azo dyes were recognized byAlPDAX with preferential affinity towards brilliant yellow azo dye. The practical application ofAlPDAX as azo dye chemosensor is also observed by evaluating the fluorescence behaviour ofAlPDAX against mixture of 'brilliant yellow' azo dye and coloured food items in which azo dye are used as adulterants. Abstract : Al 3+ ‐ phenanthroline xerogel is designed and synthesized and performs dual function as catalyst for Knoevenagel condensation and as fluorogenic template for detection of azo dyes.